The role of interior design elements in providing a cognitively stimulating toddler space in Filipino households - Ramos, Jacob Andre E.
Cognitive stimulation involves engaging two or more senses, allowing children to develop cognitive classifications of stimuli. This qualitative descriptive study aimed to describe the role of visual (lighting, color) and tactile (furniture, floor and wall finishes) interior design elements in providing a cognitively stimulating toddler space in selected Filipino households. Seven middle-class families in Laguna with toddlers aged one to three were purposely selected. Seven respondents, one parent per household, participated in a survey and interview during the observation of interior spaces. Ocular inspections included measuring areas for floor plans and documenting interior elements through an observation guide and photographs. Data were analyzed thematically. Findings showed that the main toddler spaces were the living area and the parents’ bedroom. Visual elements were selected to create a maaliwalas atmosphere, including sufficient natural light from windows, cool-toned center lights, light and neutral colors in interior surfaces, and brighter accents from toddler items. Tactile elements were chosen with toddler safety in mind, consisting of wooden and plastic furniture, ceramic tile flooring with foam mats, and painted concrete walls. Overall, the existing interior design elements contributed to the cognitive stimulation in toddler spaces, relying more on visual stimulation as respondents observed that lighting supported toddlers’ focus and visual perception, while colors evoked curiosity and excitement. In contrast, tactile stimulation was limited to furniture, as floors and walls primarily served as toddlers’ physical support. Future research may consider a larger sample size or examine auditory and olfactory stimuli.